(untitled) (Costos y Gestión, 2020)
To manage organizations and solve the particular problems that arise from reality, the technique must provide the tools, but it is also necessary to have the basic theoretical principles and postulates that provide support to costing techniques. In this sense, the General Cost Theory (TGC) tries to provide a logical structure to analyze and study a particular economic phenomenon: costs. It is important to emphasize that the theories support or use different observational models to facilitate the study and description of the problem under analysis. Consequently, it is necessary to advance in the study and establishment of the different Models used in the General Theory of Cost that help to adequately analyze the object of study. The objective of this work is to carry out a reflexive analysis on the processes of accumulation of costs, relying on the rules of a technical-organizational nature that preside over the progress of the productive processes, in order to make a proposal about the study of the cost observation models. To achieve this goal, an interpretative analysis of texts and research papers written by recognized authors in the discipline was carried out.